Mathematics teachers’ knowledge of indigenous games in teaching mathematics - Tangkur, Michael; Nabie, Michael Johnson; Ali, Clement Ayarebilla (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
We explored junior high school teachers' knowledge and the impact of indigenous games in teaching basic mathematical concepts. The researchers employed the qualitative phenomenological design to address the purpose, objectives and research questions. The accessible sampling was used to sample 70 teachers (65 males, 5 females) for phase one of the study. Out of 70 teachers, five (three males and two females) were purposively sampled for the study's second phase. Two instruments, a semi-structured interview guide and an observation checklist were used to collect data. The data was analyzed thematically to reflect the research questions. The findings of both phases revealed that most teachers had adequate knowledge of indigenous games and knew the impact of indigenous games on students’ learning of mathematics. In particular, the observation checklist showed that some teachers still adhered to the traditional approach (a direct teaching method) and required the knowledge of indigenous games to enhance their teaching skills and techniques. Therefore, in-service training, workshops and other continuous professional development should be organized to update teachers' knowledge on the effective use of indigenous games in the teaching and learning of mathematics.